An intragenic duplication in the AFF2 gene associated with Cornelia de Lange syndrome phenotype - Lucia-Campos, Cristina; Parenti, Ilaria; Latorre-Pellicer, Ana; Gil-Salvador, Marta; Bestetti, Ilaria; Finelli, Palma; Larizza, Lidia; Arnedo, María; Ayerza-Casas, Ariadna; Del Rincón, Julia; Trujillano, Laura; Morte, Beatriz; et al. (Frontiers in Genetics, 2024)
Cornelia de Lange syndrome (CdLS, OMIM #122470, #300590, #300882, #610759, and #614701) is a rare congenital disorder that affects the development of multiple organs and is characterized by physical abnormalities and cognitive and behavioral disabilities. Its molecular basis is mainly based on alterations in genes encoding structural and regulatory proteins related to the cohesin complex. Moreover, other transcriptional regulatory factors have been linked to this syndrome. However, additional causative genes are still unknown, since many patients still lack a molecular diagnosis. Herein, we describe a case with multiple affected family members presenting with an intragenic duplication in the AFF2 gene. The direct tandem intragenic duplication of exons 10, 11 and 12 was detected through high-resolution array Comparative Genomic Hybridization and next-generation sequencing technologies. Confirming the X-linked inheritance pattern, the duplication was found in the patient, his mother and his maternal aunt affected (dizygotic twins). Targeted sequencing with Oxford Nanopore Technologies revealed an aberrant transcript which is predominantly expressed in the patient and his aunt. Along with these results, a significant reduction in AFF2 gene expression levels was detected in these two individuals. Clinically both subjects exhibit a classic CdLS phenotype, whereas the mother is mostly unaffected. Consistent with the phenotypical differences observed between the mother and the aunt, there is a marked difference in X-inactivation patterns skewing. Given the crucial role of AFF2 in transcriptional regulation, it is not surprising that AFF2 variants can give rise to CdLS phenotypes. Therefore, the AFF2 gene should be considered for the molecular diagnosis of this syndrome.